TANGGUNGJAWAB TERHADAP ANGGOTA KEPOLISIAN YANG BERTUGAS MENJAGA TAHANAN DI WILAYAH HUKUM POLRES FAKFAK - Abdurrohim, Muhammad Imaduddin; Murary, Weron; Baho, Dayen (Ensiklopedia of Journal, 2025)
Abstract: The purpose of the research is related to the responsibility of members of the Police who guard prisoners in the jurisdiction of the Fakfak Police and the law against members of the police who guard prisoners because of the negligence of the prisoners who escape, where the suspect or defendant is detained during the investigation, prosecution and examination process at the court hearing. The type of research used in this study is empirical juridical obtained in various regulations, and is also supported by field data conducted by collecting data in the field through interviews. The sources of data in this study are legal materials consisting of laws and regulations, legal materials consisting of books, legal journals, opinions of scholars (doctrines), legal cases, jurisprudence, and the results of the latest symposiums, which are related to research problems, legal materials that provide clues or explanations of primary legal materials and secondary legal materials, such as explanations of legislation, legal encyclopedias, etc.  and the Law Magazine Index. The responsibilities of police members who guard detainees in the jurisdiction of the Fakfak Police include law enforcement and security, protection of human rights, and the application of sanctions for negligence. Although there are regulations regulating disciplinary and criminal sanctions, the effectiveness of this law enforcement is still influenced by various factors such as legal understanding and community culture. Law enforcement against police members who are negligent in guarding detainees so that prisoners escape still face various challenges. Although there are criminal provisions in the Criminal Code, the sanction that is more often applied is the internal police discipline sanction. Factors such as the lack of understanding of the law and community culture also affect the effectiveness of this law enforcement. Therefore, efforts are needed to increase legal understanding among police officers and the application of stricter sanctions in accordance with applicable legal provisions.Keywords: Responsibility, Police, Guarding Prisoners, Fakfak Police